EXPLORING UNIVERSITY STUDENTS’ PERCEPTION AND PREFERENCE IN READING DIGITAL AND PRINTED TEXTS - Tracy, Nafissa; Kadarizman, A. Effendi; Dzulfikri, Dzulfikri; Giffari, Wildana M. (Research and Development Journal of Education, 2025)
The rapid shift to digital learning media has sparked debate over which medium students prefer and understand better for reading. Digital texts provide easier access and convenience; however, studies increasingly indicate cognitive costs associated with such Reading for deeper processing. This study explores university students’ attitudes and preferences toward digital versus print Reading, with a particular focus on the attitudes and life experiences associated with each format. Using a mixed-methods design, questionnaire data were gathered from 62 ELLs and supported by semi-structured interviews with several participants. The results support a clear preference for printed text, especially when reading for prolonged periods and annotating. Surveyed students are not alone in reporting that concentration, comprehension, and memory retention all improve when reading from printed rather than digital materials because of extraneous cognitive load; dual-processing theories suggest that more extraneous mental effort may be required in a written rather than a digital environment. However, the research suggests that students find digital texts convenient for Reading preparation and for flexible contributions to seminar discussion. Differences among these perceptions highlight the interaction among cognitive, affective, and situational factors that influence Reading preferences. The research concludes that the two formats have complementary roles; however, hard copy remains preferred for extended academic Reading. Pedagogical implications: Students can benefit from format-specific Reading approaches in order to maximize their gains.